Physical and Non-Physical Factors Analysis of The Sukaramai Medan Traditional Market and Their Effect On The Area Accessibility Conditions - Elisabeth Simorangkir; Novrial (Talenta Publisher, 2022)
Sukaramai Medan Traditional Market has several problems that happened during its development. One of the crucial issues is congestion caused mainly by traders who use the road to sell. From the compilation of data, Sukaramai Medan Traditional Market shows that it is getting busier and chaotic. Still, so far, there has been no significant improvement even though it interferes with user activity. This research was conducted to determine the problems in Sukaramai Medan Traditional Market based on physical and non-physical factors that affect access used as a guideline for improvement to create a more convenient area for market users. This study uses mixed methods between quantitative and qualitative methods with data collection used in the form of observations on the existing condition and surveying respondents that related. The several variables observed in the analysis are market location, trading rooms, and merchant mobility. Several physical and non-physical factors associated with congestion with the lowest value can be used as the main focus in improvement. It is the market setup and item type arrangement for physical factors, while for non-physical factors, it relates to parking area and circulation. Suppose the problems on some of these factors can be resolved. In that case, it will approach the criteria of an excellent traditional market so that the accessibility of the surrounding area will be better